ANALYSIS OF T. COLIFORM AND E. COLI BACTERIAL CONTAMINATION IN REFILLABLE DRINKING WATER DEPOTS IN NORTH SUMATRA PROVINCE - Nanda, Meutia; Mrp, Mimbi Gusrera; Kurniawan, Ahadi; Saniah, Fadilatus; Suhaima, Maznil; Sari, Widia; Rinanda, Dewi; Mawarifda, Khairunrani (HEARTY, 2026)
Contamination of refill drinking water in Indonesia remains a serious public health issue. One of the main causes is weak sanitation supervision and poor hygiene practices during the water treatment process at Refill Drinking Water Depots (DAMIU). This study aims to analyze the contamination of Coliform and Escherichia coli bacteria in DAMIU across North Sumatra Province and to assess their compliance with the quality standards set by the Ministry of Health Regulation (Permenkes) No. 02 of 2023 concerning Environmental Health Quality Standards (SBMKL). The research employed a descriptive observational method with a secondary data analysis approach using microbiological laboratory test results from the Public Health Laboratory Center on 55 water samples collected from 11 districts/cities in North Sumatra Province. The results showed that most refill water samples did not meet microbiological standards, as they contained T. Coliform and E. coli exceeding the maximum limit of 0 CFU/100 ml. The highest contamination levels were found in Medan Sunggal District, Medan Selayang District, and Mandailing Natal Regency, while Toba Regency and parts of Pematang siantar City showed compliant results. The findings indicate that the majority of DAMIU in North Sumatra Province have not met microbiological quality standards, with approximately 70% of samples testing positive for T. coliform and more than 40% containing E. coli. The presence of T. coliform and E. coli in refill drinking water poses a potential risk of waterborne diseases such as diarrhea, cholera, hepatitis A, and dysentery. Therefore, regular supervision and strict implementation of hygiene and sanitatio.